Phosphonium modified clay/polyimide nanocomposites - (:unkn) unknown (IOP PUBLISHING LTD, 2014)
In this study, octyltriphenylphosphonium bromide [OTPP-Br] was prepared from the reaction of triphenylphosphine and 1-bromooctane. The modification of clay was done by ion exchange reaction using OTPP-Br in water medium. Poly(amic acid) was prepared from the reaction of 3,3',4,4'-Benzophenonetetracarboxylic dianhydride (BTDA) and 4,4'-Oxydianiline (ODA). Polyimide(PI)/clay hybrids were prepared by blending of poly(amic acid) and organically modified clay as a type of layered clays. The morphology of the Polyimide/phosphonium modified clay hybrids was characterized by scanning electron microscopy (SEM). Chemical structures of polyimide and Polyimide/phosphonium modified clay hybrids were characterized by FTIR. SEM and FTIR results showed that the Polyimide/phosphonium modified clay hybrids were successfully prepared. Thermal properties of the Polyimide/phosphonium modified clay hybrids were characterized by thermogravimetric analysis (TGA).
Keywords: MECHANICAL-PROPERTIES; MODIFIED ORGANOCLAY; COMPOSITES; ADHESION; FILMS